The Questioning Style Of (Hamza And Do) In The Hadiths Of Imam Al-Sadiq, Peace Be Upon Him - et. al., Maytham Ahmed abed Hamza Al-hameedawi, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Most of the grammatists see that the interrogation in the Arabic language performs two basic functions in eloquent linguistic use, namely: the real interrogation and the metaphorical interrogation, but it has appeared in the hadiths of Imam Ja`far al-Sadiq, "peace be upon him", two other uses are: the interrogation by which the pilgrims intend to repel the invalidated arguments, especially In the position of religion and the Creator Almighty. The second is the interrogation that performs the function of alerting, especially in the composition of (hamza + verb saw) and its conjugations such as (I saw you, I saw you, I saw you ...) which the grammatists said that this composition is for intelligence, while the hadiths of Imam Ja`far al-Sadiq, "peace be upon him," contrary to what They decided it from a base in this composition.